The Wiskott-Aldrich Syndrome: The Actin Cytoskeleton and Immune Cell Function. Issue 3 (29th May 2013) - Blundell, Michael P.; Worth, Austen; Bouma, Gerben; Thrasher, Adrian J.
Abstract : Wiskott-Aldrich syndrome (WAS) is a rare X-linked recessive primary immunodeficiency characterised by immune dysregulation, microthrombocytopaenia, eczema and lymphoid malignancies. Mutations in the WAS gene can lead to distinct syndrome variations which largely, although not exclusively, depend upon the mutation. Premature termination and deletions abrogate Wiskott-Aldrich syndrome protein (WASp) expression and lead to severe disease (WAS). Missense mutations usually result in reduced protein expression and the phenotypically milder X-linked thrombocytopenia (XLT) or attenuated WAS [1-3]. More recently however novel activating mutations have been described that give rise to X-linked neutropenia (XLN), a third syndrome defined by neutropenia with variable myelodysplasia [4-6]. WASP is key in transducing signals from the cell surface to the actin cytoskeleton, and a lack of WASp results in cytoskeletal defects that compromise multiple aspects of normal cellular activity including proliferation, phagocytosis, immune synapse formation, adhesion and directed migration.